Crowdsourcing Relative Rankings of Multi-Word Expressions: Experts versus Non-Experts - David Alfter; Therese Lindström Tiedemann; Elena Volodina (Northern European Journal of Language Technology, 2022)
In this study we investigate to which degree experts and non-experts agree on questions of linguistic complexity in a crowdsourcing experiment. We ask non-experts (second language learners of Swedish) and two groups of experts (teachers of Swedish as a second/foreign language and CEFR experts) to rank multi-word expressions in a crowdsourcing experiment. We nd that the resulting rankings by all the three tested groups correlate to a very high degree, which suggests that judgments produced in a comparative setting are not inuenced by professional insights into Swedish as a second language.